Pelatihan Untuk Meningkatkan Kemampuan Berbicara Dalam Bahasa Inggris Bagi Siswa SD/SMP/SMA Di Dusun Tawun Desa Sekotong Barat Kecamatan Sekotong - Aini Husnida Wulandari; Sugianto, Riris (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
The growth of tourist attractions in the Sekotong Barat Subdistrict needs a boost in human resources, particularly in English proficiency. As the region experiences ongoing development, evident in the improved infrastructure of special attractions like Gili Nanggu, Gili Sudak, Gili Tangkong, Gili Kedis, Kemos Beach, Elak-Elak Beach, Tawun Pier, and more, it becomes crucial to attract both local and international tourists. Enhancing human resources involves offering English language courses and cultivating a skilled workforce capable of tapping into the village's potential, serving as guides for tourists. It also entails empowering the youth to actively contribute to government initiatives in the tourism sector. The efforts to improve English communication skills, particularly through language courses, align with the UTM Community Service Institute's objectives and have shown positive results in West Sekotong Village, notably within the Tawun Hamlet community, over the course of a six-week service period.